Inferential Transitions. Issue 3 (3rd July 2018) - Quilty-Dunn, Jake; Mandelbaum, Eric
ABSTRACT: This paper provides a naturalistic account of inference. We posit that the core of inference is constituted by bare inferential transitions (BITs), transitions between discursive mental representations guided by rules built into the architecture of cognitive systems. In further developing the concept of BITs, we provide an account of what Boghossian [2014] calls 'taking'—that is, the appreciation of the rule that guides an inferential transition. We argue that BITs are sufficient for implicit taking, and then, to analyse explicit taking, we posit rich inferential transitions (RITs), which are transitions that the subject is disposed to endorse.